2013
DOI: 10.5704/moj.1307.007
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Femoral Neck Fractures: Unipolar Versus Bipolar Hemiarthroplasty

Abstract: Background and objective:Intracapsular femoral neck fractures are common in the elderly population. To avoid the poor outcome of internal fixation and for early mobilization, hemiarthroplasty is performed. However, there is inadequate evidence to support the choice between unipolar or bipolar hemiarthroplasty. The aim of this study was to compare the outcome of unipolar with the bipolar prosthesis in geriatric patients. Methods: Forty-one patients above 60 years of age and an acute displaced fracture of the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The follow-up period varied from 6 to 204 months. Eighteen studies did not report the number lost during follow-up 6,11,22,27,32–37,4144,5053 .…”
Section: Resultsmentioning
confidence: 99%
“…The follow-up period varied from 6 to 204 months. Eighteen studies did not report the number lost during follow-up 6,11,22,27,32–37,4144,5053 .…”
Section: Resultsmentioning
confidence: 99%
“…This observation is different from that was found in many studies comparing unipolar and bipolar prosthesis. In a study by Somashekar, SVK et al [24], which compared the outcome of unipolar with the bipolar prosthesis in geriatric patients the mean Harris hip score in bipolar and unipolar groups was 86.18±12.18 and 79.79±15.55, respectively (p=0.183); range of motion was 210.63±28.39 and 181.58±37(p=0.015) with bipolar and unipolar groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that GARDEN type IV fractures are completely displaced and there is no contact between the femoral head and the femoral neck (49). Studies have shown that with bipolar hip hemiarthroplasty, the management of displaced femoral neck fractures was associated with a better mean score and the incidence of complications was limited (50).…”
Section: Discussionmentioning
confidence: 99%